Access to Daylight and Views Improves Physical and Emotional Wellbeing of Office Workers: A Crossover Study - Woo, May; MacNaughton, Piers; Lee, Jaewook; Tinianov, Brandon; Satish, Usha; Boubekri, Mohamed (Frontiers in Sustainable Cities, 2021)
While buildings are designed with expansive windows to allow for abundant daylight and views, in practice, they are frequently occluded to control for heat and glare. Electrochromic glass windows are a solution designed to maximize occupant access to daylight and views throughout the day, and previous research has demonstrated the benefits it can impart on sleep and cognition. We extend this research to quantify its impacts on the perceived physical and emotional wellbeing of occupants in an office environment. 30 office workers spent five days working in each of two West-facing offices that were identical with the exception of the window treatment: one with dynamic electrochromic windows and the other with functionally standard windows partially occluded by a fixed roller shade. When working in the office with electrochromic glass, participants were 8-fold more likely of report satisfaction with daylight conditions and 6.5-fold more likely to report satisfaction with views of the outside, were 48% less likely to report eyestrain, perceived a significant benefit to positive affect and were 77% less likely to report feeling depressed. This study adds to the growing body of research demonstrating the importance of daylighting strategies in designing spaces that support the physical and mental health of occupants.